The natural anticancer compound rocaglamide selectively inhibits the G1‐S‐phase transition in cancer cells through the ATM/ATR‐mediated Chk1/2 cell cycle checkpoints. Issue 8 (21st October 2013) - Neumann, Jennifer; Boerries, Melanie; Köhler, Rebecca; Giaisi, Marco; Krammer, Peter H.; Busch, Hauke; Li‐Weber, Min
<x xml:space="preserve">Abstract</x> Targeting the cancer cell cycle machinery is an important strategy for cancer treatment. Cdc25A is an essential regulator of cycle progression and checkpoint response. Over‐expression of Cdc25A occurs often in human cancers. In this study, we show that Rocaglamide‐A (Roc‐A), a natural anticancer compound isolated from the medicinal plant Aglaia, induces a rapid phosphorylation of Cdc25A and its subsequent degradation and, thereby, blocks cell cycle progression of tumor cells at the G1‐S phase. Roc‐A has previously been shown to inhibit tumor proliferation by blocking protein synthesis. In this study, we demonstrate that besides the translation inhibition Roc‐A can induce a rapid degradation of Cdc25A by activation of the ATM/ATR‐Chk1/Chk2 checkpoint pathway. However, Roc‐A has no influence on cell cycle progression in proliferating normal T lymphocytes. Investigation of the molecular basis of tumor selectivity of Roc‐A by a time‐resolved microarray analysis of leukemic vs. proliferating normal T lymphocytes revealed that Roc‐A activates different sets of genes in tumor cells compared with normal cells. In particular, Roc‐A selectively stimulates a set of genes responsive to DNA replication stress in leukemic but not in normal T lymphocytes. These findings further support the development of Rocaglamide for antitumor therapy.